2017
DOI: 10.1186/s41241-016-0009-1
|View full text |Cite
|
Sign up to set email alerts
|

A study on genetic polymorphism in Matrix Metalloproteinases-3 in oral submucous fibrosis patients and in healthy individuals

Abstract: Background: OSF is a potentially malignant condition affecting the oral cavity and oropharynx. MMP-3 also known as Stromelysin -I is a key member of the MMP family which is responsible for degradation of collagen type II,IV,V,IX and X, proteoglycans, gelatins, fibronectin, laminin and elastin. It plays an important role in activation of pro MMP-1 into the active form of MMP-1 in malignant tissues. MMP-3 expression is low in normal tissues but it is altered during tumour formation, where remodeling of ECM is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…and some other study suggested to be around 30%. 27,28 Previously, polymorphic MnlI restriction endonuclease site of COL1A1 and polymorphic PvuII restriction endonuclease site of COL1A2 are situated in exon 25, reported to be associated with OSMF risk but profound mechanism associated with OSMF pathogenesis is unknown. 9 Moreover, the contribution of collagen polymorphism in association with OSCC is not reported so far despite the elevated level of collagen-type mRNA.…”
Section: Discussion and Con Clus I Onmentioning
confidence: 99%
“…and some other study suggested to be around 30%. 27,28 Previously, polymorphic MnlI restriction endonuclease site of COL1A1 and polymorphic PvuII restriction endonuclease site of COL1A2 are situated in exon 25, reported to be associated with OSMF risk but profound mechanism associated with OSMF pathogenesis is unknown. 9 Moreover, the contribution of collagen polymorphism in association with OSCC is not reported so far despite the elevated level of collagen-type mRNA.…”
Section: Discussion and Con Clus I Onmentioning
confidence: 99%